2007
DOI: 10.1016/j.eplepsyres.2007.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Cluster analysis detection of functional MRI activity in temporal lobe epilepsy

Abstract: Purpose-The objective of this pilot study was to evaluate the ability of a novel method of cluster analysis, 2dTCA, for identifying and characterizing peak fluctuations in fMRI BOLD signals in the temporal lobes and the default-mode network in temporal lobe epilepsy (TLE) without EEG.Methods-BOLD fMRI images were acquired in seventeen TLE patients and compared to EEG. The timing of significant transient BOLD peaks was estimated by 2dTCA, and activation maps were determined.Results-Sixteen subjects (94%) showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 52 publications
2
24
0
Order By: Relevance
“…Comparable efforts were undertaken at the EEG level, also paying special attention to artifacts (Huiskamp, 2005;Siniatchkin et al, 2007a), or the accurate detection and classification of IED Flanagan et al, 2009;Jann et al, 2008;Liston et al, 2006a;Marques et al, 2009;SalekHaddadi et al, 2006;Vulliemoz et al, 2010b;Zijlmans et al, 2007), vigilance effects and ongoing spontaneous 'background' EEG (Moehring et al, 2008;Siniatchkin et al, 2007b;Tyvaert et al, 2008b). Finally, analysis methods found entry into EEG-fMRI which had already been established in 'classical' neuroimaging studies including data driven methods such as independent component analysis Moeller et al, 2011;Rodionov et al, 2007;Siniatchkin et al, 2007b) and others with and without using EEG information for the detection of epileptiform activity with fMRI (Donaire et al, 2009;Hamandi et al, 2005;Morgan et al, 2007;Morgan et al, 2004). Using this variety of analysis methods, mainly more recently, ictal activity itself was investigated with EEG-fMRI (Auer et al, 2008;Bai et al, 2010;Berman et al, 2010;Bonaventura et al, 2006;Detre et al, 1996;Di Bonaventura et al, 2006;Donaire et al, 2009;Federico et al, 2005a;Kobayashi et al, 2006c;LeVan et al, 2010;Liu et al, 2008;Marrosu et al, 2009;Moeller et al, 2010;Salek-Haddadi et al, 2009;SalekHaddadi et al, 2002;Tyvaert et al, 2008a).…”
Section: Eeg-fmri Applications In Epilepsymentioning
confidence: 99%
“…Comparable efforts were undertaken at the EEG level, also paying special attention to artifacts (Huiskamp, 2005;Siniatchkin et al, 2007a), or the accurate detection and classification of IED Flanagan et al, 2009;Jann et al, 2008;Liston et al, 2006a;Marques et al, 2009;SalekHaddadi et al, 2006;Vulliemoz et al, 2010b;Zijlmans et al, 2007), vigilance effects and ongoing spontaneous 'background' EEG (Moehring et al, 2008;Siniatchkin et al, 2007b;Tyvaert et al, 2008b). Finally, analysis methods found entry into EEG-fMRI which had already been established in 'classical' neuroimaging studies including data driven methods such as independent component analysis Moeller et al, 2011;Rodionov et al, 2007;Siniatchkin et al, 2007b) and others with and without using EEG information for the detection of epileptiform activity with fMRI (Donaire et al, 2009;Hamandi et al, 2005;Morgan et al, 2007;Morgan et al, 2004). Using this variety of analysis methods, mainly more recently, ictal activity itself was investigated with EEG-fMRI (Auer et al, 2008;Bai et al, 2010;Berman et al, 2010;Bonaventura et al, 2006;Detre et al, 1996;Di Bonaventura et al, 2006;Donaire et al, 2009;Federico et al, 2005a;Kobayashi et al, 2006c;LeVan et al, 2010;Liu et al, 2008;Marrosu et al, 2009;Moeller et al, 2010;Salek-Haddadi et al, 2009;SalekHaddadi et al, 2002;Tyvaert et al, 2008a).…”
Section: Eeg-fmri Applications In Epilepsymentioning
confidence: 99%
“…proposed by Morgan et al to improve the sensitivity and reduce the impact of physiological noise in detecting an epilepsy focus [30,31] . A more recent study suggested that, although simulated data showed a potential advantage of 2D-TCA over EEG-fMRI in detecting activity restricted to deep brain structures, patient data did not show such results [32] .…”
Section: Introductionmentioning
confidence: 99%
“…This was a result of the fact that in TCA, as only a single histogram is created, one is unable to differentiate between the different forms of activity that occur during a given scan, including epileptic and artefactual activity. To overcome this, Morgan et al developed 2D-TCA (Morgan et al, 2007), a modified version of TCA that creates multiple histograms, or reference time courses, for a given scan based on the timing of activity; each of these time courses may then be assumed to result from a different source and used to create separate activation maps. The initial study found that it performed better than TCA in detecting epileptic activity as it was less susceptible to other forms of activity.…”
Section: Introductionmentioning
confidence: 99%